Short-term exposure to PM2.5 and its components and type 2 diabetes-related hospital admissions, length of stay, and hospital costs in Shanghai. - Liang, Hongyu; Zhou, Wenyong; Wen, Zexuan; Wei, Jing; Wang, Weibing; Li, Jun (International Journal of Environmental Health Research, 2025)
The short-term influence of particles with an aerodynamic diameter ≤2.5 μm (PM2.5) and its individual elements on hospital costs, the length of hospital stay (LOS), and hospital admissions caused by type 2 diabetes remains unclear. A generalized additive model (GAM) with quasi-Poisson distribution was utilized to assess the association of individual pollutants and mixtures. For every 10 μg/m3 rise in PM2.5 and a per-SD increase in NH4+at lag0, hospital admissions increased by 0.93% (95% CI: 0.68, 1.19) and 2.81% (95% CI: 2.20, 3.42); hospital costs rose by 24.58 thousands of CNY (95% CI: 5.95, 43.22) and 77.06 thousands of CNY (95% CI: 33.07, 121.04); LOS increased by 9.53 days (95% CI: 0.44, 18.62) and 27.80 days (95% CI: 6.34, 49.27), respectively. Factor analysis showed that mixed-source particulate pollution was significantly associated with an increase in hospital admissions (0.27%, 95% CI: (0.20, 0.34)), LOS (2.87 days, 95% CI: (0.35, 5.40)), and hospital costs (71.68 thousands of CNY, 95% CI: (19.89,123.46)). These findings suggested that short-term exposure to elevated levels of PM2.5 as well as its components increased the risk of hospital costs, LOS, and hospital admissions due to type 2 diabetes.